A Study on Immunosuppressant Induced Dyslipidemia and Associated Chronic Graft Rejection in Renal Transplant Recipients - P. Samuel Gideon George, K. Dhivya (Journal of Applied Pharmaceutical Science, 2016)
Dyslipidemia is a common complication of renal transplantation referred to as new onset dyslipidemia. Immune suppressants, in particular cyclosporine, the calcineurin inhibitor and others are known to cause dyslipidemia through non-competitive inhibition of sterol 27-dehydroxylase (CYP27A1). On the other hand, dyslipidemia has been found to be associated with higher graft rejection due to decrease in immune suppressant activity and direct graft destruction. Hence the study was designed to analyze the effect of dyslipidemia on chronic allograft rejection. Clinical and biochemistry reports of 142 renal transplant recipients were collected in designed case report forms. All statistical analysis was carried out using International Business Machine (IBM) Statistical Package for Social Sciences (SPSS) 17.0. Immunosuppressive therapy, comorbid diabetes and hypertension, age and serum creatinine were found to be the common predictors of dyslipidemia whereas as dyslipidemia, age and gender were found to be predictors of graft destruction and loss (P>0.05). Incidence of graft loss was found higher in dyslipidemic patients (P
Keywords: Renal transplant, immunosuppressant, metabolic syndrome, dyslipidemia, graft rejection.